Odpowiedzi

Najlepsza Odpowiedź!
2010-04-13T19:42:05+02:00
A)y=2t-1 \+1
y+1=2t /2
(y+1)2=t zapisz to w ulamku

b) v=atkwadrat\t *t
vt=at(kwadrat) \pierwaistek z t kwadrat
v*t kwadrat=a
c)P=abx \/ab
p\ab=x
d)S=a/bx x
sb=a/x
sb\a=x

1 3 1
2010-04-13T19:45:06+02:00
Y=2t-1
y+1=2t/:2
y+1/2=t

v= at(kwadrat) /t /*t
vt=at(kwadrat)/t(kwadrat)
vt/t(kwadrat)=a


P = abx /ab
P/ab=x
1 2 1
2010-04-13T19:48:56+02:00
A)
y=2t-1
y+1=2t
y+1/2=t

b) oblicz : t
v=at^
v/a=t^
pierwiastek z v/a = t

oblicz : a
v=at^
v/t^=a
pierwiastek z v/t = a

c)
P=abx
p/ab=x

d)
S=a/bx
Sbx=a
sb/a=x